A phase II clinical trial of topotecan and carboplatin in patients with newly diagnosed advanced epithelial ovarian cancer. Issue 2 (1st February 2007) - Vecchione, F.; Fruscio, R.; Dell'Anna, T.; Garbi, A.; Garcia Parra, R.; Corso, S.; Lissoni, A. A.
Abstract : A phase II clinical trial conducted to evaluate the efficacy and tolerability of topotecan and carboplatin as first-line therapy for women with advanced epithelial ovarian cancer was the objective of this study. Patients had histologically confirmed ovarian epithelial cancer with at least one measurable lesion. Patients received topotecan 1.5 mg/m 2 on days 1–3 and carboplatin at an area under the curve (AUC) of 5 on day 3 every 21 days for six cycles. All 42 patients enrolled were evaluable for response and toxicity. Median number of cycles delivered was six. Overall response rate was 71%, with 19 clinical complete responses (45%) and 11 clinical partial responses (26%). Median survival time was 47 months and 5-year survival was 42%. Myelosuppression was the predominant toxicity, with grade 3 or 4 neutropenia occurring in 100% of patients. However, this toxicity was transient and easily manageable; no patients experienced febrile neutropenia. The combination of topotecan and carboplatin is active in advanced epithelial ovarian cancer. Delay of therapy by 1 week or topotecan dose reduction to 1.25 mg/m 2 is the first-choice option to reduce topotecan toxicity without affecting the efficacy. Moreover, a chemotherapy regimen using weekly topotecan, which is currently being tested, should be considered.